ANALISIS KUALITAS LAYANAN BANK SYARIAH DENGAN MENGGUNAKAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DI MAKASSAR - Andi Pawennari; Irma Nur Afiah; Verawati Verawati; Muhammad Nusran; Muhammad Fakhri Arham (Universitas Mathla’ul Anwar Banten, 2021)
The development of Islamic banking in the face of a highly competitive business environment in order to stay afloat is by developing customer service well, where the customer's perception of a quality becomes a benchmark for each agency or company. Bank Sulselbar branch of sharia located in Makassar is engaged in providing services to the community so that they are very concerned about comfort and service to the community. Through the Serquel method and Importance Performance Analysis we can find out the quality of service and handling complaints against customer loyalty through consumer satisfaction.Based on the results of the study with the Importance Performance Analysis method, most of the attributes are negative. Based on the analysis, there are 10 attributes that satisfy the user that the company must maintain so that it can maintain customer loyalty, that is; assist customers in conducting transactions, help customers who experience difficulties without being asked for help, provide fast service to customers when making transactions, be responsive in meeting customer needs in transactions, have good knowledge of types of banking services and products, always prioritizing hospitality in providing services to customers, always prioritizing politeness in providing services to customers, being a trusted place in saving money, always being kept clean and comfortable and always looking neat and polite. Conclusion of this research is that the performance of company must be maintained so that it can maintain customer loyalty.